Googled - "Auletta, Ken." (New York)
Includes bibliographical references (p. [339]-372) and index. Messing with the magic -- Starting in a garage -- Buzz but few {Dollar}'s -- Prepping the Google rocket -- Innocence or arrogance? -- Google goes public -- The new evil empire? -- Chasing the fox -- War on multiple fronts -- Waking the government bear -- Google enters adolescence -- Is old media drowning? -- Compete or collaborate? -- Happy birthday -- Googled -- Where is the wave taking old media? -- Where is the wave taking Google? -- Media maxims.
Keywords: GOOGLE (FIRM);INTERNET INDUSTRY -- UNITED STATES.;WEB SEARCH ENGINES -- UNITED STATES -- HISTORY.;INTERNET SEARCHING